Hearing protection of noise-cancelling earphones in dental clinics - Prof Je Seon Song; Dr Da Young Cho; Prof. Jinsei Jung (Elsevier, 2023)
Aim or Purpose: The aim of this study is to evaluate the effect that noise canceling earphones can have on the hearing of dentists by wearing noise canceling earphones during noise-induced dental treatment. Materials and Methods: The subjects of the study were randomly assigned to an experimental group (24 dentists wearing earphones) and a control group (23 dentists not wearing earphones). To evaluate the hearing ability of the subjects, pure tone audiometry and distortion product otoacoustic emission tests were performed at the first visit, 6 months, and 1 year later. The experimental group was instructed to wear noise-canceling earphones (HS-01, SuhyunTech, Hwaseong, South Korea) during noise-induced dental treatment. Results: As a result of this study, the group wearing earphones showed a decrease in pure tone average (PTA) which indicates improvement in hearing, while the control group showed an increase in PTA. In the case of the distortion product otoacoustic emission test, there was a significant increase in the group wearing earphones, indicating improvement in hearing, and showed a significant decrease in the control group. Conclusions: This suggests that noise-cancelling earphones helps protect hearing, and exposure to dental noise without hearing protection for a long period of time can cause hearing loss.